The compact wheelchair roller dynamometer - Fernandes Melo Oliveira, S.; Guimaraes Bione, A. A.; Guedes Leite Oliveira, L. I.; Veronese da Costa, A.; de Sá Pereira Guimaraes, F. J.; da Cunha Costa, M. (Sports Medicine International Open, 2017)
The equipment for evaluating the propulsion of a wheelchair is very complex and expensive. To validate a new dynamometer prototype for assessing the propulsion capacity of wheelchairs, 21 healthy subjects (age: 20.9±2.4 yr; weight: 68.9±7.9 kg; height: 174.0±7.1 cm; BMI: 22.7±2.5 kg·m-2) who do not normally require wheelchairs performed a sprint protocol for 20 s after a 1-min warm-up. The power and rotation data acquired by the prototype (both right and left sides) were compared with those of a reference system via high-speed videography (240 fps). The results showed high levels of accordance (95% CI), excellent values for the intraclass correlation coefficient (ICC: .99; P<0.00), no significant differences in the rotation (P=0.91) and power (P=0.94) between the methods. The proposed equipment met the validation criteria and thus can be applied as a new tool for assessing wheelchair propulsion.